Gut-microbiome-based predictive model for ST-elevation myocardial infarction in young male patients - Liu, Mingchuan; Wang, Min; Peng, Tingwei; Ma, Wenshuai; Wang, Qiuhe; Niu, Xiaona; Hu, Lang; Qi, Bingchao; Guo, Dong; Ren, Gaotong; Geng, Jing; Wang, Di; et al. (Frontiers in Microbiology, 2022)
Background: ST-segment elevation myocardial infarction (STEMI) in young male patients accounts for a significant proportion of total heart attack events, clinical awareness and asymptomatic screening for AMI at younger age are urgently needed. The gut microbiome is potentially involved in the pathogenesis of STEMI. The aim of present study is to develop an early risk prediction model based on gut microbiome and clinical parameters for this population. Methods: A total of 81 young male subjects (age < 44 years) including 41 STEMI patients and 40 non-CAD controls were enrolled in this study. The Illumina sequencing of 16S rRNA-based gut microbiome were performed to identify the microbial markers between these two groups. Subsequently, nomogram and corresponding web page were constructed with K-fold cross-validation, calibration curves and decision curve analysis (DCA) to evaluate their efficacy and practicability. Results: Compared with non-CAD control, the young male patients with STEMI showed substantial decreased tendency regarding α and β diversity and were identified significantly altered gut microbiome represented by Streptococcus and Prevotella. In clinical information, the STMEI patients tend to have higher BMI, SBP, TG, ALT and AST with lower BUN. Additionally, both BMI and SBP were positively correlated with Streptococcus and [Ruminococcus] and negatively correlated with Prevotella and Megasphaera (p＜0.05). Prevotella is the only gut microbiome that showed negative correlation with AST (p＜0.05). Finally, an early predictive nomogram and corresponding web page were constructed based on gut microbiome and clinical parameters with an area under the ROC curve of 0.877 and a C-index of 0.911. For the internal validation, the stratified K-fold cross-validation (K = 3) was as follows: area under the curve, 0.934. The subsequent calibration curves of the model showed good consistency between the actual and predicted probabilities. Then the DCA showed indicating a high net clinical benefit (NCB) in clinical practice. Conclusions: Combination of gut microbiome and common clinical indicators, this study provided a useful and non-invasive tool which supports the potential clinical validity for prediction of STEMI in young male population.